Courts of the peace within the legal system of the Republic of Poland - Lach, Rafał (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The purpose of this study is not a detailed analysis of the proposed legal solutions concerning Courts of the peace, especially since at the time of writing this article the legislative process is at an early stage. On November 4, 2021, the Sejm received the draft Act on Magistrates’ Courts presented by the President of the Republic of Poland, the first reading of which took place on December 2, 2021, as well as the draft provisions introducing the Act on Magistrates’ Courts. The presidential project is not the only one being processed. Despite this, it is worth making a preliminary analysis of the proposed assumptions, as well as possible future objections that may be raised after the adoption of the regulations, because the basic issues are unlikely to change radically. Regardless of this, the study is an attempt to initially determine the possible consequences of introducing the described legal solutions to the legal system for the judiciary.